Proinflammatory Cytokines and Periodontal Disease - Nada Tawfig (Journal of Dental Problems and Solutions - Peertechz Publications, 2016)
Numerous biological procedures are strictly controlled by cell-cell interactions, which are categorized into two forms: cognate (adhesive) interactions, attained by mutual recognition between membrane-bound cell-surface molecules; and cytokine-mediated interactions [1]. Cytokines (Greek cyto-, cell; and -kinos, movement) are a category of signaling molecules that are used extensively in cellular communication. The responses caused by these substances are diverse and interrelated. Generally, cytokines control growth, mobility and differentiation of lymphocytes, but they also exert a similar effect on other leukocytes and some non-immune cells [2].